From morality to rules to choices: introducing and testing a new theory on how morals influence cooperation - Gavassa Pérez, Ernesto María (2022)
This thesis presents a framework that I name the MRC framework, as its purpose is to capture how people go from Morality to Rules to Choices. I embed two theories, Blame Avoidance and Praise Seeking, within the MRC framework. The former states that subjects are impelled to avoid what they consider as blameworthy strategies from an impartial perspective, given all the circumstances that surround their evaluation of such strategies. The latter states that subjects are impelled to seek doing what they consider as the most praiseworthy strategies from an impartial perspective, given all the circumstances that surround their evaluation of such strategies. The chief characteristic feature that distinguishes my new models from those present in the literature is that they explore the motivational force of prosociality from an impartial perspective, thereby replacing the characteristic self-centredness of most models of other-regarding preferences within the literature. My theories and classical models of other-regarding preferences need not be either orthogonal or theories making different predictions. Rather, what I contend is that their ultimate explanation for the flourishing of prosocial behaviour is radically different. Whereas social preferences contend that subjects are moved by their self-interest, howsoever enlightened and altruistically inclined, our theories propose that self-interest plays a minor role, if any at all, in prosocial considerations. As a first step towards this end, the thesis focuses on studying how these newly developed theories fare at explaining behaviour at public goods games, a canonical form of a social dilemma. The thesis contains three core chapters – chapter 2, chapter 3, and chapter 4 – plus an introduction (chapter 1) and a conclusion (chapter 5). The first of those (chapter 2) starts by developing an elicitation tool that allows us to measure empirically the moral judgments of a person, from an impartial perspective. Chapter 3 uses the newly developed tool and the theories proposed to test the explanatory of the MRC framework in predicting unconditional contributions and contribution attitudes to give-some and take-some public goods. Chapter 4 goes beyond the scope of chapter 3 and makes a direct test of the MRC framework against several canonical models of social preferences at the individual level: material selfishness, inequality aversion, reciprocity, social efficiency, maximin, and spite. The test explores the explanatory power of each of the theories at predicting contribution attitudes of a social dilemma (MPCR <1) and a common interest game (MPCR >1). Our results show that (i) social dilemmas are perceived as moral issues (chapter 2); (ii) blame avoidance can predict contribution attitudes of both give and take social dilemmas, and blame avoidance and praise seeking can predict unconditional contributions in give and take social dilemmas (chapter 3); and (iii) that blame avoidance, along with inequality aversion and maximin, is among the three best performing theories in predicting contribution attitudes to social dilemmas and common interest games (chapter 4).